2019
DOI: 10.22207/jpam.13.3.05
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pseudomonas aeruginosa Quorum Sensing by Curcuma xanthorrhiza Roxb. Extract

Abstract: Microorganisms such as Pseudomonas aeruginosa have always been adaptable in surviving the harsh environment such as antimicrobial agents via the quorum sensing (QS) mechanism. Studies have shown that quorum sensing mechanism cases have been highly associated with foodborne illnesses. Since synthetic compounds such as azithromycin (AZM) are reported to have detrimental effects on human, using medicinal local plants have been gaining attention as an anti-quorum agent. The aim of this study was to determine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…However, certain phenolic compounds amongst other metabolites in these plants could be responsible for the observed anti-QS activity. Naturally occurring phenolic compound p-coumaric acid has already been shown to interact with bacterial quorum sensing, sometimes by triggering or by inhibiting the QS-process system (Othman et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, certain phenolic compounds amongst other metabolites in these plants could be responsible for the observed anti-QS activity. Naturally occurring phenolic compound p-coumaric acid has already been shown to interact with bacterial quorum sensing, sometimes by triggering or by inhibiting the QS-process system (Othman et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The study of the different types of turmeric species in the Zingiberaceae family [2][3][4]7] regarding the content of bioactive compounds suggests a growing trend in the production of curcumin in the coming years due to the development of new areas of use (Figure 2). Due to its antioxidant and anti-inflammatory properties, curcumin is presented in many specialized studies as a potential adjuvant for treating cancer [6] and neurodegenerative diseases [21].…”
Section: Methods Of Obtaining and Antiviral Antifungal And Antibacter...mentioning
confidence: 99%
“…Considering the epidemiological events caused by the appearance of the COVID-19 virus, in the last two years, there has been an intensification of studies on the methods to obtain [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] curcumin and its bioactivity properties [21][22][23][24][25][26][27][28][29][30]. If, in 2017, the global curcumin market was valued at USD 52.45 million, due to the diversification of application areas, it is estimated that the size of the global curcumin market will reach USD 151.9 million by 2027.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that C. xanthorrhiza extract has shown to inhibit acid production of S. mutans biofilm [53]. Moreover, C. xanthorrhiza extract is also reported to have anti-QS or quorum quenching activity [69]. The high level of tannin, phenol, phenolic compound in C. xanthorrhiza is suggested to precipitate the proteins that are vital for rhl system in Pseudomonas aeruginosa.…”
Section: Antibiofilmmentioning
confidence: 99%
“…The high level of tannin, phenol, phenolic compound in C. xanthorrhiza is suggested to precipitate the proteins that are vital for rhl system in Pseudomonas aeruginosa. By inhibiting the rhl system, the swarming activity of P. aeruginosa is inhibited, thus the QS will not take place [69,70]. Besides that, killing the cells by cell lysis will also degrade and detach the biofilm.…”
Section: Antibiofilmmentioning
confidence: 99%